Pengaruh Partisipasi Masyarakat terhadap Peningkatan Mutu Pendidikan di SMK Negeri 1 Robatal Kabupaten Sampang Melalui Profesionalisme Guru - Chamariyah Chamariyah; Mohammad Faisol Akbar; Mei Indrawati (Journal of Management and Creative Business, 2025)
This type of research uses cross-sectional research, the research approach uses a quantitative approach. The research sample was 50 respondents. The aim of this research is 1) To test and analyze whether community participation has a significant influence on improving the quality of education at SMK Negeri 1 Robatal, Sampang Regency. 2) To test and analyze whether community participation has a significant influence on the professionalism of teachers at SMK Negeri 1 Robatal, Sampang Regency. 3) To test and analyze whether teacher professionalism has a significant influence on the quality of education at SMK Negeri 1 Robatal, Sampang Regency. 4) To test and analyze whether community participation has a significant indirect influence on the quality of education at SMK Negeri 1 Robatal Sampang Regency through teacher professionalism. The research results show that: 1) Community participation has a significant positive effect on the quality of education at SMK Negeri 1 Robatal Sampang Regency with an original sample value of 0.252. 2) Community participation has a significant positive effect on the professionalism of teachers at SMK Negeri 1 Robatal Sampang Regency with an original sample value of 0.619.3) Teacher professionalism has a significant positive effect on the quality of education at SMK Negeri 1 Robatal Sampang Regency with an original sample value of 0.603. 4) Indirectly, community participation has a significant effect on the quality of education at SMK Negeri 1 Robatal, Sampang Regency, which is mediated by teacher professionalism, so that the seventh hypothesis is accepted with an original sample value of 0.373.